Molecular modulator for stable inverted planar perovskite solar cells with efficiency enhanced by interface engineering. Issue 31 (25th July 2019) - Zhao, Z. Q.; You, S.; Huang, J.; Yuan, L.; Xiao, Z. Y.; Cao, Y.; Cheng, N.; Hu, L.; Liu, J. F.; Yu, B. H.
Abstract : A novel interface-management strategy has been developed. Benefiting from optimized energy level alignment and interface contact, the Ca(acac)2 -based layer significantly enhances the performance of PSCs, yielding an impressive efficiency of 20.15%. Abstract : Hybrid organic/inorganic organometal halide perovskite solar cells (PSCs) have been attracting enormous research interest. However, their performance improvement and engineering at the molecular level remain challenging for the inverted structures. Surface traps present in semiconductor films critically influence ultimate photovoltaic behaviors. A solution-processable and stable cathode buffer layer that can passivate surface traps is thus of great importance for the application of PSCs. Here, we successfully fabricated high performance and stable inverted planar PSCs by employing calcium acetylacetonate (Ca(acac)2 ), a molecular modulator, as the cathode interfacial layer (CIL). The average power conversion efficiencies of PSCs based on different perovskite photoactive layers were improved. Strikingly, FA0.85 MA0.15 Pb(I0.85 Br0.15 )3 -based and MAPbI3 -based PSC devices were found to have champion power conversion efficiencies of 20.15% and 18.23%, respectively. Importantly, Ca(acac)2 -modified PSCs also have high stability. Their power conversion efficiencies decreased by only 15% after 30 days of storage and they show much suppressed hysteresis compared with the control devices (without interfacial modification).